2022
DOI: 10.1021/accountsmr.2c00130
|View full text |Cite
|
Sign up to set email alerts
|

Solution Processing of Cross-Linked Porous Organic Polymers

Abstract: Conspectus Porous organic polymers (POPs), essentially including polymers with intrinsic microporosity (PIMs), conjugated microporous polymers (CMPs), covalent organic frameworks (COFs), hyper-cross-linked polymers (HCPs) and so on, have recently attracted broad interest in many application areas because of their structural diversity and functional tunability. However, except for linear PIMs that can dissolve in organic solvents for solution processing into membranes, most POPs are highly cross-linked (hereaft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…This value is also better than that of the reported 2D‐COFs such as TTA‐TTB‐COF (5 g g −1 ), [ 32 ] TJNU‐201 (5.62 g g −1 ), [ 33 ] TPT‐DHBDX‐COF (5.43 g g −1 ), [ 35 ] TPT‐Azine‐COF (2.19 g g −1 ), [ 39 ] and SCOF (4.41 g g −1 ). [ 40 ] The work was also comparable to those of progressive 2D COFs such as TJNU‐203 (5.89 g g −1 ), [ 30 ] C‐TP‐BPDA‐COF (6.11 g g −1 ), [ 29 ] PB‐TT COF (5.97 g g −1 ), [ 42 ] COF‐AB‐50 (10.2 g g −1 ), [ 43 ] TAPB‐PDA COF (7.7 g g −1 ), [ 44 ] and QTD‐COF (6.3 g g −1 ). [ 45 ] In addition, iodine‐loaded COFs (COFs@I 2 ) kept their weight upon exposure to air under ambient conditions at 25 °C for 6 days.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…This value is also better than that of the reported 2D‐COFs such as TTA‐TTB‐COF (5 g g −1 ), [ 32 ] TJNU‐201 (5.62 g g −1 ), [ 33 ] TPT‐DHBDX‐COF (5.43 g g −1 ), [ 35 ] TPT‐Azine‐COF (2.19 g g −1 ), [ 39 ] and SCOF (4.41 g g −1 ). [ 40 ] The work was also comparable to those of progressive 2D COFs such as TJNU‐203 (5.89 g g −1 ), [ 30 ] C‐TP‐BPDA‐COF (6.11 g g −1 ), [ 29 ] PB‐TT COF (5.97 g g −1 ), [ 42 ] COF‐AB‐50 (10.2 g g −1 ), [ 43 ] TAPB‐PDA COF (7.7 g g −1 ), [ 44 ] and QTD‐COF (6.3 g g −1 ). [ 45 ] In addition, iodine‐loaded COFs (COFs@I 2 ) kept their weight upon exposure to air under ambient conditions at 25 °C for 6 days.…”
Section: Resultssupporting
confidence: 59%
“…Solid adsorbents are a simple way due to their simplicity, effectiveness, and recyclability. [26][27][28][29][30] Recent progress has shown that the COFs with high porosity, stability, and functional skeleton were potential candidates for iodine vapor uptake. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Yin and co-authors reported that the hollow microspheres of COF improved iodine vapor capturability via higher effective volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COF‐based materials will be more widely used in functional solid‐phase matrices in the future. [ 291 ] Similarly, a new 2D ultra‐microporous phosphate‐based COF has great application potential in the selective adsorption of uranium. [ 292 ] Figure a shows a COF‐based micro‐solid phase extraction.…”
Section: Applications Of 2d Organic Materialsmentioning
confidence: 99%
“…The essence of the formation of soluble GDY is to weaken the interlayer stacking forces and enhance framework–solvent interactions of nanosheets to allow self-exfoliation via electrostatic repulsion to obtain high solubility in certain solvents with retaining the GDY basic skeleton. 14 Interlayer engineering has been key in preparing expanded interlayer and monolayer nanosheets in expansion–exfoliation, simultaneously tuning properties and improving performances. 15 This method can readily intercalate or trap substantial charge species into the inter-layer skeletons to reduce the two adjacent-layer interactions.…”
Section: Introductionmentioning
confidence: 99%